Narrativas infantis e processo formativo : estudo sobre as significações de crianças sobre suas experiências na educação infantil - Coelho, Ellen Cristine Campos de Souza (2016)
This study is the result of a research for a Master’s Degree, in the Education Program at the Federal University of Mato Grosso. It brings a focus on Children’s Narratives as a source of knowledge and as an investigative path, in order to understand children’s experiences in the context of Pre-Kindergarten. The aim was to understand the processes of meaning in children’s educational experience, through their narrative production. The investigation was carried out in a public school located in the city of Rondonópolis, in the State of Mato Grosso. The participants of the research were specifically children aged between four and five. The procedures of data collection were: videos, photographs and written registers, specifically notes based on the observation of the children’s interactions and of the teacher’s practice. In addition to these, iconographic registers to meet the uniqueness of each child; narrative interviews with the teacher of the group and with the children; documents and the pedagogical project for the second school term were used as research material. All the procedures resulted in valuable narrative texts which gave this study the necessary data. Stemming from the intention of the investigation, which is based on the meaning the children give to the experiences they have in school, the qualitative approach was the chosen methodological frame, having as basic reference authors, such as André (2005), Bogdan and Biklen (1994), and Poupart (2008). But it was found necessary to recur to narrative research, in accordance with the authors Clandinin and Connely (2010). In considering contemporary studies about children and childhood, the dialogue among Omar (2010), Bazilio and Kramer (2011), Sarmento (2003), Ariés (1981), Kishimoto (2007), Prado (1999), Andrade (2007), and others who research the subject has been rich. On school culture, we adopt the concept presented by Vinão Frago (2000); and to make reference to the understanding of the concept of experience, support was sought in Dewey (2011). In respect to the concept of narrative space, our work is based on the propositions made by Andrade and Teibel (2012). In relation to the contributions of the studies regarding formation processes and their importance as bridges built from knowledge shared in the Children’s context, we used Sarmento, Domingues and Mizukami (2009), and Sarmento and Marques (2006). In this research, the results show that to think about childhood is to seek, in the whole historical context, the construction of meanings attributed to it, that in several periods clues are left of the way it was and, currently, how it is understood by society. It also points to the need to understand that the children have their own culture in which they mean and build meanings of their experiences in the context of Pre-Kindergarten. By giving them a place in speech, movement, participation in the children’s narratives presented here, it was possible to observe the narrative spaces and the places built by the children which in turn, as social practice, are formative experiences that promote for the little ones, their peers, and the teachers cultural experiences in the context of the school where the study was done.